An integrated strategy combining DNA walking and NGS to detect GMOs. (1st October 2017) - Fraiture, Marie-Alice; Herman, Philippe; Papazova, Nina; De Loose, Marc; Deforce, Dieter; Ruttink, Tom; Roosens, Nancy H.
Highlights: A strategy coupling DNA walking and NGS is proposed to prove the presence of GMOs. Its performance was assessed using samples typically encountered in routine analysis. It detects even trace-level GM events in grain, processed, and GMO mixture samples. At a practical level, this new system's workflow is very simple and rapid. At an analytical level, no specific bioinformatics expertise is required. Abstract: Recently, we developed a DNA walking system for the detection and characterization of a broad spectrum of GMOs in routine analysis of food/feed matrices. Here, we present a new version with improved throughput and sensitivity by coupling the DNA walking system to Pacific Bioscience® Next-generation sequencing technology. The performance of the new strategy was thoroughly assessed through several assays. First, we tested its detection and identification capability on grains with high or low GMO content. Second, the potential impacts of food processing were investigated using rice noodle samples. Finally, GMO mixtures and a real-life sample were analyzed to illustrate the applicability of the proposed strategy in routine GMO analysis. In all tested samples, the presence of multiple GMOs was unambiguously proven by the characterization of transgene flanking regions and the combinations of elements that are typical for transgene constructs.